2006
DOI: 10.1021/jo0524268
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2,3-Disubstituted Benzo[b]selenophenes via Electrophilic Cyclization

Abstract: 2,3-Disubstituted benzo[b]selenophenes have been prepared by the electrophilic cyclization of various 1-(1-alkynyl)-2-(methylseleno)arenes by Br2, NBS, I2, ICl, PhSeCl, PhSeBr, and Hg(OAc)2. This method tolerates a wide variety of functional groups, including alcohol, ester, nitrile, nitro, and silyl groups, and proceeds under exceptionally mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(69 citation statements)
references
References 54 publications
2
67
0
Order By: Relevance
“…Recently, Larock and co-workers reported that 2,3-disubsti- [17] Inspired by Larock's reaction, we extended this method to access new fused chalcogenophenes 4a-e. Gratifyingly, we found that the electrophilic cyclization of 3-alkynyldihydroselenophenes with I 2 in CH 2 Cl 2 as the solvent at room temperature afforded the desired fused chalcogenophenes 4a-e in moderated to good yields (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Larock and co-workers reported that 2,3-disubsti- [17] Inspired by Larock's reaction, we extended this method to access new fused chalcogenophenes 4a-e. Gratifyingly, we found that the electrophilic cyclization of 3-alkynyldihydroselenophenes with I 2 in CH 2 Cl 2 as the solvent at room temperature afforded the desired fused chalcogenophenes 4a-e in moderated to good yields (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…This methodology takes advantage, in most cases, by the presence of a halogen atom suitable to suffer further transformations. This cyclization has been used as an efficient tool in the synthesis of highly substituted indoles, [11] furans, [12] thiophenes, [13] selenophenes, [14] benzo[b]furans, [15] benzo [b]thiophenes, [16] benzo [b]selenophenes, [17] lactones, [18] and pyrroles [19] by employing electrophiles like I 2 , ICl, or chalcogen derivatives. [20] These and especially the knowledge that 3-alkynyldihydroselenophenes are promising candidates for electrophilic cyclization reactions to form fused selenophenes prompted us to develop a complete investigation on the synthesis of 3-alkynyldihydroselenophenes from 3-iododihydroselenophenes as the sequence showed in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“… a Reaction Condition A: All reactions were performed using 0.30 mmol of the alkyne, 5 equiv of NaX, and 5 equiv of CuSO 4 •5H 2 O in 5 mL of EtOH at room temperature for 24 h. b Isolated yields. c Literature yield via halocyclization. d reference 23b. e reference 24. f reference 26 …”
Section: Figurementioning
confidence: 99%
“…26 Herein we disclose the first ever report of this chlorocyclization reaction starting with 2-alkynylmethylselenobenzene 12 using table salt and the green solvent ethanol (Table 1, entry 10). The resulting 3-chlorobenzo[ b ]selenophene 22 was obtained in a good yield of 72%.…”
mentioning
confidence: 96%
See 1 more Smart Citation